Strategi Guru PAI dalam Pembentukan Karakter Religius Siswa Kelas XI di SMA N 9 Padang - Pratama, Dio Putra; Rivauzi, Ahmad (Lembaga Yasin AlSys, 2024)
This research aims to find out the PAI teacher's strategy in teaching the formation of religious character in class XI students at SMA Negeri 9 Padang, the PAI teacher's strategy in cultivating the religious character of class Padang. The method used in this research is qualitative method. The research data sources were Islamic Religious Education teachers and class XI students at SMA N 9 Padang. The data collection techniques for this research include observation, interviews and documentation. All interview results were then analyzed systematically through three phases, namely (Data Reduction, Data Presentation and Drawing Conclusions). The results of the research show that the PAI teacher's strategy in teaching students' religious character takes the form of enriching religious content in class and strengthening Islamic school culture. The enrichment program carried out by PAI teachers is in the form of improving student learning achievement, preventing students from getting bored studying in class, and making it easier for students who are slower learners. Meanwhile, the implementation of Islamic culture in schools takes the form of reading prayers before studying, the Koran, Duha prayers, 5s culture, congregational prayers. The strategy used by teachers to raise awareness of students' religious character is to provide habituation and role models to students. The habits carried out are checking students' neatness, going to school on time, praying and memorizing short letters before learning begins, midday prayers, midday prayers in congregation. Meanwhile, providing a good example to students in the form of teachers entering class to teach on time, having a neat appearance, carrying out midday and noon prayers in congregation, teachers having good morals and obeying the rules. The strategies used by PAI teachers in monitoring students' religious character include providing rewards and punishments to students and taking attendance for five daily prayers and religious activities.